2016
DOI: 10.1002/chem.201603700
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Metallocenes on Silica

Abstract: The adsorption of the metallocenes ferrocene, doubly deuterated ferrocene, cymantrene and nickelocene, as well as molybdenum hexacarbonyl, proceeds in the absence of a solvent. Large single pieces of silica gel were placed in contact with the solid metallocenes and the adsorption process was visualized on a macroscopic scale and the maximal loadings were determined. H, H, and C solid-state NMR studies confirmed fast isotropic reorientation of the surface-adsorbed metallocene molecules within the pores of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…Although the chemistry of metallocenes adsorbed on silica gel has not been well investigated, very recently Cluff and Blümer studied the adsorption of ferrocene on silica gel by solid‐state NMR spectroscopic methods, and discovered that in the presence of air, adsorbed ferrocene is oxidized to ferrocenium salts at acidic surface silanol sites . Based on this observation, we hypothesize that our aerobic oxidation could proceed through initial electron‐transfer from iron to a dioxygen molecule, thereby forming ferrocenium ion I and superoxide radical anion intermediate, O 2 .…”
Section: Resultsmentioning
confidence: 93%
“…Although the chemistry of metallocenes adsorbed on silica gel has not been well investigated, very recently Cluff and Blümer studied the adsorption of ferrocene on silica gel by solid‐state NMR spectroscopic methods, and discovered that in the presence of air, adsorbed ferrocene is oxidized to ferrocenium salts at acidic surface silanol sites . Based on this observation, we hypothesize that our aerobic oxidation could proceed through initial electron‐transfer from iron to a dioxygen molecule, thereby forming ferrocenium ion I and superoxide radical anion intermediate, O 2 .…”
Section: Resultsmentioning
confidence: 93%
“…Indeed,t he 31 Pw ideline and MAS spectra ( Figure 9) of 4a show that the CSA is only reduced, but not averaged out entirely.T he size of the molecule andt he long alkyl chains are not expected to slow the motion of an adsorbed species because it has been demonstrated earlier that paraffin, cyclododecane, or metallocenes with cycloalkyl substituents are highly mobile on silica and other surfaces. [13][14][15][16] Upon adsorption of 4 to form 4a all CSA parameters and the span of the signal are changed significantly,t he latter by nearly 100 ppm (Table2). Therefore, it can be concluded that both P=Og roups in the molecule are interacting equallyw ith the surfaceo fs ilica, but they actually do impedee ach other's mobility to some extent.…”
Section: C and 31 Ps Olid-state Nmr Spectroscopymentioning
confidence: 99%
“…Encouraged by the meaningful results obtained with 1 Hw ideline NMR of adsorbed metallocenes [12][13][14][15][16] andm obile species in polymers [50] we probed 4 and 4a with this technique. The proton wideline spectrum of 4 shows as ignal that is broadened by large homonuclear dipolar interactions [17][18][19] and spans from about À110ppm to + 120 ppm, with ah alfwidth of ca.…”
Section: C and 31 Ps Olid-state Nmr Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations